2020
DOI: 10.18632/aging.103290
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional changes of gut microbiota in ovariectomized rats and their correlations with altered bone mass

Abstract: As a critical factor involved in the maintenance of physiological homeostasis, the gut microbiota (GM) reportedly plays a key role in bone development. To date, the association between the GM and steroid deficiency-induced osteoporosis remains poorly understood. Forty female Sprague Dawley rats were divided into an ovariectomy (OVX) or control group. We performed 16S rRNA and metagenome sequencing, to compare diversity, taxonomic differences, and functional genes. The GM composition did not change in the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 50 publications
3
27
0
Order By: Relevance
“…In fact, several key genera such as Prevotella , Barnesiella , Lactococcus , Streptococcus and Ruminococcus correlating to serum indexes of bone homeostasis and inflammation (TNF-α and IL-17) have been reported ( 21 ). Here, we detected a significant correlation of Ruminococcus with RANK, OPG and TRACP ( Table 1 ) as reported by Ma et al ( 45 ), implying that ICA can modulate GM to influence serum indexes to regulate bone metabolisms. Moreover, ICA administration-induced improvement of intestinal barrier function has been proven to be associated with GM by inhibiting NF-κB or p38 MAPK signaling pathway ( 25 , 26 ).…”
Section: Discussionsupporting
confidence: 87%
“…In fact, several key genera such as Prevotella , Barnesiella , Lactococcus , Streptococcus and Ruminococcus correlating to serum indexes of bone homeostasis and inflammation (TNF-α and IL-17) have been reported ( 21 ). Here, we detected a significant correlation of Ruminococcus with RANK, OPG and TRACP ( Table 1 ) as reported by Ma et al ( 45 ), implying that ICA can modulate GM to influence serum indexes to regulate bone metabolisms. Moreover, ICA administration-induced improvement of intestinal barrier function has been proven to be associated with GM by inhibiting NF-κB or p38 MAPK signaling pathway ( 25 , 26 ).…”
Section: Discussionsupporting
confidence: 87%
“…In a study related to Clostridiales, MA et al performed 16S rRNA and metagenome sequencing using forty female rats randomly divided into ovariectomy or control groups. The experiment found that there was a high abundance of Clostridium in the ovariectomy group and that Ruminococcus belonging to the same order might be the pathogenic bacteria of steroid deficiency-induced osteoporosis (Ma et al, 2020b). The same conclusion was reported in a clinical study by NI et al They identified specific bacteria taxa that regulated bone mass variations via a Mendelian randomization approach and found that Clostridiales and Lachnospiraceae were negatively associated with heel bone density (Ni et al, 2021).…”
Section: Firmicutessupporting
confidence: 56%
“…Thus, in an experimental design that incorporates behavioral outcomes, pair-housing is preferable (Pinelli et al, 2017). Intestinal-produced microbial betaglucuronidase and beta-glucosidase are part of the estrobolome, and affect the circulation of E2 in the body by reactivating the compound (Ervin et al, 2019;Ma et al, 2020). In addition, enhanced beta-glucuronidase levels in blood plasma and serum have been associated with the occurrence of breast cancer (Whitaker, 1960;Minton et al, 1986), reinforcing the presence of a relationship between functional changes of the intestinal microbiota, breast cancer, and menopause (Trichopoulos et al, 1972;Beaud et al, 2005;Gagnière, 2016).…”
Section: Conclusion Limitations and Future Perspectivesmentioning
confidence: 99%